Greater Integration of the Environmental Sector in CGIAR's One Health Activities Following the Emergence and Global Spread of the Novel Coronavirus Called SARS-CoV-2 - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Origins of recent zoonotic epidemics link the research themes of human, animal and environmental health: the three tenets of One Health. Within CGIAR, the environmental sector has not been fully integrated into One Health. In 2020, a major report, Preventing the Next Pandemic argued for better ways of achieving trans-disciplinarity in One Health. The report, alongside targeted CGIAR communication around One Health, has resulted in more partnerships with environmental institutions and a strengthened CGIAR influence in One Health.